PERENDAMAN EKSTRAK DAUN JERUJU (Acanthus ilicifolius) UNTUK MENINGKATKAN IMUNITAS DAN SINTASAN UDANG VANAME (Litopenaeus vannamei) YANG TERINFEKSI BAKTERI Vibrio parahaemolyticus: Soaking In Jeruju Leaf Extract (Acanthus ilicifolius) To Enhance Immunity And Survival Rates In Vaname Shrimp (Litopenaeus vannamei) Infected With The Bacterium Vibrio parahaemolyticus - Devan Rengga Purwanto; Ni Nyoman Dian Martini; Jasmine Masyitha Amelia (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
White shrimp (Litopenaeus vannamei) is a leading aquaculture commodity in Indonesia whose production is often hampered by Vibrio parahaemolyticus infection, the causative agent of Acute Hepatopancreatic Necrosis Disease (AHPND) with mortality reaching 85–100%. This study aimed to determine the effect of immersion in jeruju leaf extract (Acanthus ilicifolius) on the immune response and survival of V. parahaemolyticus-infected white shrimp, and to identify its optimal concentration. A Completely Randomized Design (CRD) was used with five groups: negative control, positive control, and extract immersion at 200, 300, and 400 mg/L for 30 minutes. Data were analyzed using One Way ANOVA followed by Duncan's test. Results showed that jeruju leaf extract immersion significantly affected (p<0.05) THC, DHC composition (an increase in the proportion of granular cells), and post-infection survival rate. The 400 mg/L concentration (treatment C) produced the best results, with the highest THC of 15.08 × 10⁶ cells/ml, the highest proportion of granular cells at 65.67%, and the highest SR of 79.17%, compared to only 48.33% in the positive control. These findings demonstrate that jeruju leaf extract has potential as an environmentally friendly herbal immunostimulant for controlling V. parahaemolyticus infection in white shrimp aquaculture.